Edukasi dan Pelatihan Penanaman Hydroponik, Solusi Pemanfaatan Lahan Sempit Pemukiman Padat - Lazuardi El Ghiffary; Ardi Alfaris; Wardah Nailah Azis; Ali Mubin (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Hydroponic planting education and training is an activity carried out to answer the needs of residents for the problem of decreasing agricultural land which makes food in the market very volatile. The hydroponic farming system provides an alternative solution for residents to be able to garden without having to have a large area of land. This education and training introduces the hydroponic farming method starting from planting media, seedlings, maintenance and harvesting. As a result of this education and training, the community can begin to understand the importance of utilizing the narrow land in residential areas as a farming area with hydroponic methods.